Integrated land use planning for sustainable agriculture and rural development (Apple Academic Press, 2015)
Part 1. Soil and land resource information and land degradation assessment -- part 2. Application of geo-informatics in land use planning -- part 3. Planning for sustainable agriculture, land use in different agro-ecosystems -- part 4. Integrated land use planning and institutional arrangements.